2001
DOI: 10.1139/g01-082
|View full text |Cite
|
Sign up to set email alerts
|

Multiple flowering time QTLs within severalBrassicaspecies could be the result of duplicated copies of one ancestral gene

Abstract: Quantitative trait locus (QTL) analysis was used to study the evolution of genes controlling the timing of flowering in four Brassica genomes that are all extensively replicated. Comparative mapping showed that a chromosomal region from the top of Arabidopsis thaliana chromosome 5 corresponded to three homoeologous copies in each of the diploid species Brassica nigra, B. oleracea, and B. rapa and six copies in the amphidiploid B. juncea. QTLs were detected in two of the three replicated segments in each diploi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
43
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(43 citation statements)
references
References 27 publications
0
43
0
Order By: Relevance
“…It is interesting to determine whether loci controlling these common traits are derived from homologous parts of the genome. Quantitative trait loci controlling the flowering time of several Brassica species were reported in homologous parts of the genomes (Axelsson et al 2002). Since a large number of the present primer sets enabled to identify microsatellite loci in these cucurbit crops, homology studies using these microsatellite loci may provide information on the loci controlling these common traits, and clarify the relationships among the genomes of these species.…”
Section: Application Of Melon Microsatellite Markers To Cucurbit Speciesmentioning
confidence: 93%
“…It is interesting to determine whether loci controlling these common traits are derived from homologous parts of the genome. Quantitative trait loci controlling the flowering time of several Brassica species were reported in homologous parts of the genomes (Axelsson et al 2002). Since a large number of the present primer sets enabled to identify microsatellite loci in these cucurbit crops, homology studies using these microsatellite loci may provide information on the loci controlling these common traits, and clarify the relationships among the genomes of these species.…”
Section: Application Of Melon Microsatellite Markers To Cucurbit Speciesmentioning
confidence: 93%
“…Integration of SSR markers into the present linkage map could be useful for MAS for bolting time in breeding programs of Brassica plants. Furthermore, since Brassica species are closely related to the model plant Arabidopsis, in which the flowering-time pathways have been extensively studied, the flowering-time genes from Arabidopsis could be used as RFLP probes for mapping the loci in Brassica species (Teutonico and Osborn 1994, Kole et al 2001, Axelsson et al 2001. Because many of the genes related to flowering time have been identified and classified into a few functional pathways, including the photoperiod and vernalization promotion pathways in Arabidopsis (Koornneef et al 1998, Simpson et al 1999, the understanding of how the effects of QTL alleles were altered by environmental factors will provide clues for the identification of the candidate genes responsible for bolting time in B. rapa.…”
Section: Qtl Analysis For Bolting Timementioning
confidence: 99%
“…Therefore, although bolting time was evaluated in the present study, flowering time was more frequently used for QTLmapping because of the simplicity of the measurement. QTLmapping for flowering time in B. rapa was reported in several populations (Teutonico and Osborn 1995, Osborn et al 1997, Axelsson et al 2001. These studies showed that QTL-mapping is a useful method for analyzing such traits.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Genomic synteny has been found to be well conserved among a broad array of species, even though genomic size in plant exhibits a wide diversity, e.g., 125 Mb for A. thaliana to 125 Gb for Fritillaria assyriaca (Bennett and Smith 1976). Physically and functionally conserved gene(s), known as orthologs and paralogs, were also identified (Axelsson et al 2001). Because Brassica and Arabidopsis are in the same family, the Cruciferae, the level of synteny between them provides a good opportunity to study how genetic and morphological variation has developed during the evolution of the genome, including the endurance of certain genetic structures in Arabidopsis and related Brassica species.…”
mentioning
confidence: 99%